Haematological, biochemical and immunological biomarkers, antibacterial activity, and survival in Nile tilapia Oreochromis niloticus after treatment using antimicrobial peptide LL-37 against Streptococcus agalactiae - de Sousa, Elielma Lima [UNESP]; Assane, Inácio Mateus [UNESP]; Santos-Filho, Norival Alves [UNESP]; Cilli, Eduardo Maffud [UNESP]; de Jesus, Raphael Barbetta [UNESP]; Pilarski, Fabiana [UNESP] (Elsevier, 2021)
Among the antimicrobial peptides (AMPs), which act as natural antibiotics in preventing the colonization of pathogens, LL-37 is noteworthy. It is a human cathelicidin characterized as a broad-spectrum antibiotic, with chemotactic and immunomodulatory properties. This study aimed to evaluate the antimicrobial activity and therapeutic effectiveness of peptide LL-37 against streptococcosis caused by Streptococcus agalactiae in Nile tilapia and to assess some of its potential adverse effects (in vivo haematological, biochemical, and immunological profiles) in the fish. After in vitro cytotoxicity studies of LL-37 against Nile tilapia red blood cells (RBCs) and antimicrobial susceptibility testing (minimum inhibitory concentration and minimum bactericidal concentration, MIC and MBC, respectively) against Aeromonas hydrophila and S. agalactiae, fish were divided into six experimental groups. G1 and G2 were challenged by intraperitoneal injection with S. agalactiae and received a single oral dose of LL-37 (15 mg/kg bw) and florfenicol (FFC) (15 mg/kg bw), respectively. G3 was challenged with S. agalactiae and received a single intraperitoneal dose of LL-37 (15 mg/kg bw). The other groups were controls for infection (G4) and antimicrobial administration (G5 and G6). LL-37 showed weak hemolytic activity against Nile tilapia RBCs (24.4% lysis at 625 μg/mL) and strong in vitro antimicrobial activity against S. agalactiae (MIC and MBC = 31.25 μg/mL). No significant effects were observed in the haematological, biochemical, and immunological profiles of fish medicated with LL-37 or FFC, compared to the control fish. Twenty days after the challenge, survival rates were 33.38% (G1), 38.51% (G2), 23.12% (G3), 25% (G4), and 100% (G5 and G6). Despite the strong in vitro antimicrobial activity, both antimicrobials were ineffective to control streptococcosis caused by S. agalactiae in Nile tilapia. These findings suggest that administration of LL-37 (15 mg/kg bw) is safe for Nile tilapia but not effective to control streptococcosis.
Keywords: Antimicrobial peptide; Fish disease; Oreochromis niloticus; Streptococcus agalactiae